Inside and over urban buildings: will urban agriculture spark the next urban design revolution? - René Davids (Cogent Arts & Humanities)
As the population continues to grow and the demand for food increases, the expansion of farming poses a threat to the existing forests and wildlands essential for retaining biodiversity worldwide and combating climate change. Therefore, it is essential to implement innovative strategies that optimize food production while effectively utilizing limited land resources. Despite challenges such as the frequent unavailability of vacant lots, and or buildings that can host farming activities, and inadequate supportive policies, urban farming offers numerous advantages. These benefits include enhancing food security, promoting public health, and reducing pollution associated with food transportation. Additionally, urban agriculture can mitigate the urban heat island effect, improve water retention, and foster biodiversity. However, current research on the impact of urban agriculture on city design remains alarmingly insufficient. After examining historical and contemporary urban projects that integrate agriculture into urban layouts through diagrams, author descriptions, and critical analyses, this paper argues for creating a connected network of farms within and on top of the existing urban buildings. This approach addresses not just the food requirements of the urban population but also uniquely contributes to preserving our built heritage. The case for urban agriculture is not just compelling; it is essential for our cities’ future and our planet’s health.